2015
DOI: 10.1083/jcb.201412030
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2–dependent actin bundling promotes secretory granule docking to the plasma membrane and exocytosis

Abstract: Annexin A2 and the actin cytoskeleton are essential partners in providing lipid platforms for granule recruitment and fusion during exocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 56 publications
2
67
0
Order By: Relevance
“…With this dense actin network, granules near the plasma membrane, including NPY–mCherry-containing granules, were more associated with the F-actin network than those far from the plasma membrane (Fig. 4c), similar to a recent report with three-dimensional electron tomography24. We did not observe consistently actin rings surrounding NPY–EGFP-containing vesicles (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…With this dense actin network, granules near the plasma membrane, including NPY–mCherry-containing granules, were more associated with the F-actin network than those far from the plasma membrane (Fig. 4c), similar to a recent report with three-dimensional electron tomography24. We did not observe consistently actin rings surrounding NPY–EGFP-containing vesicles (Fig.…”
Section: Resultssupporting
confidence: 90%
“…4b), confirming a dense cortical actin network observed near, but not far from, the plasma membrane (see also Supplementary Fig. 9a,b for quantification)222324. With this dense actin network, granules near the plasma membrane, including NPY–mCherry-containing granules, were more associated with the F-actin network than those far from the plasma membrane (Fig.…”
Section: Resultssupporting
confidence: 68%
“…It is worth to mention that annexin‐A2 has also been identified among the spectrin interacting partners . Annexin‐A2 is a cytosolic protein that triggers the formation of actin bundles essential for the formation of active exocytotic sites in stimulated chromaffin cells . Whether spectrin is a hub involved in the recruitment to the exocytotic sites of the actin‐binding proteins (N‐WASP, annexin‐A2) required for building the actin architecture necessary for exocytosis remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for a long time actin filament network was uniquely considered to be a physical barrier preventing the reserve pool of secretory vesicles to gain access to the plasma membrane. However, today this view has evolved toward a dynamic role of actin in which a complex process of actin filament remodeling is critically required for efficient exocytosis . Particularly, we have shown that neuronal Wiskott–Aldrich Syndrome protein (N‐WASP) is recruited at exocytic sites where its ability to promote actin filament assembly is necessary for exocytosis …”
Section: Introductionmentioning
confidence: 99%
“…Bovine chromaffin cells were washed with Locke's solution and processed for catecholamine release measurements by amperometry as described previously . Carbon‐fiber electrode of 5 μm diameter (ALA Scientific) was held at a potential of +650 mV compared with the reference electrode (Ag/AgCl) and approached closely to GFP expressing cells.…”
Section: Methodsmentioning
confidence: 99%